Kontrak pintar; analisis syariah dan parameter = Smart contract; shariah analysis and parameter - Mohamed Shaarani, Ahmad Zikrullah; Mohammad, Fidlizan; Mohd Noor, Azman; Osman, Mohd Farihal (UTM Press, Universiti Teknologi Malaysia, 2023)
Smart Contract is one of the new technological developments related to the Industrial Revolution 4.0 which emphasizes on the execution of contracts between two parties automatically based on the terms and conditions that have been agreed before. This concept minimizes the role of intermediaries that exist in traditionally executed contracts thus leading to positive effects such as cost reduction, saving time and money, less cases of fraud, manipulation and so on. Looking at the philosophy of smart contracts, it is in line with the Maqasid / Objectives of Syariah. However, the nature of this concept which relies on automation which means lack of human intervention in executing the content of the contract raises questions about shariah compliancy in the operationalization of this system especially regarding the function and eligibility of the computer system as a contracting parties rather that human, as well as what is fiqh adaptation for such concept, in addition to what is parameters and dawābit that is required to ensure that each product based on smart contracts is Shariah compliant in terms of its content, shariah monitoring process once the contract is executed, and other related issues. This study is based on a full library research where the concept of smart contracts is analyzed based on the framework of Shariah law in Muamalat, in addition to the latest technological developments related to it. The results of the study found that smart contract is an acceptable concept in Islam, but it needs some guidance and improvement to ensure it really coincides with the parameters required by Shariah, namely full compliance with the pillars and conditions of the contract, must also be in line with Maqasid al-Shariah and current applicable law, the existence of elements of compassion, consideration, tolerance/Tasāmuh and others. _________________________________________________________